Imaging CO 2 reinjection into basalts at the CarbFix2 reinjection reservoir (Hellisheiði, Iceland) with body-wave seismic interferometry - Hassing, S.H.W. (author); Draganov, D.S. (author); Janssen, M.T.G. (author); Barnhoorn, A. (author); Wolf, K.H.A.A. (author); van den Berg, J.J. (author); Friebel, M. (author); van Otten, Gijs (author); Poletto, Flavio (author) (Geophysical Prospecting, 2024)
As part of the Synergetic Utilisation of CO (Formula presented.) storage Coupled with geothermal EnErgy Deployment project, investigating CO (Formula presented.) reinjection with different seismic methods, both passive and active seismic surveys have been conducted at the geothermal power plant at Hellisheiði, Iceland. During the 2021 survey, two geophone lines recorded noise for a week. We process the passive-source data with seismic interferometry to image the subsurface structure around the CarbFix2 reinjection reservoir. To improve image quality, we perform an illumination analysis to select only noise panels dominated by body-wave energy. The results show that most noise panels are dominated by air-wave energy arriving from the direction of the power plant. We use panels with a near-vertical incidence to create a zero-offset image and a larger selection of body-wave-dominated panels to create virtual common-shot gathers. We process the gathers with a simple reflection seismology processing workflow to obtain stacked images. The zero-offset images show a relatively lower signal-to-noise ratio and only horizontal reflectors. The stacked images show slightly dipping reflectors and possibly lateral amplitude variations around the expected injection region. This could indicate a region of interest for future research into the reinjection reservoir. Applied Geophysics and Petrophysics Lab Geoscience and Engineering